Development of Android-Based Interactive Multimedia on Mushroom Material in High School - Veni Wulandari; Aunurrahman Aunurrahman; Indri Astuti; Urai Salam; Dede Suratman (Postgraduate, University of Mataram, 2024)
This research aims to produce Android-based interactive multimedia products that are feasible to use, easy for students to learn, and assist students in learning and improve student learning outcomes independently. This type of development research used the Dick, Carey & Carey developer design model. The test subjects consisted of a study teacher, six expert validators, and thirty-two students of X grade. Sampling used a purposive sampling technique, by using consideration of student scores, which were divided into three namely, high, low, and medium categories. The instruments used involved trial questionnaires, test questions, and student response questionnaires. Each of which had been validated and analyzed with the content validity of Aiken's V (Vcount ≥ Vtable). The research results show media expert validation with a score of 3.9 (valid and suitable for use), design expert validation with a score of 4.1 (very valid and highly suitable for use), and subject matter expert validation with a score of 4.1 (very valid and highly suitable for use). The results of individual test, small group test, and field test obtained an average result of 89.6% in the very positive category. Based on test performed by students, the results show that interactive multimedia development designs can be used to facilitate students to learn with an average percentage score of 85% (Very Positive Category). The feasibility of each of these processes shows that the Android-based interactive multimedia profile meets the requirements as a medium that can assist students in learning. The results of the effectiveness test also stated that interactive multimedia on Android-based had an effect and could improve students' cognitive learning outcomes with an N-Gain Score = 0.61 (Medium Category) and an Effect Size value = 2.322 (Category = Strong). The conclusion is based on the results of expert validation and product test, the Bio-Fungi learning application is feasible for use as a learning medium in the teaching and learning process and to improve students' cognitive learning outcomes.